2008
DOI: 10.1002/syn.20494
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic morphology on neurons from prefrontal cortex, hippocampus, and nucleus accumbens is altered in adult male mice exposed to repeated low dose of malathion

Abstract: Malathion is a highly neurotoxic pesticide widely used in daily life. Acute and chronic toxicity from this organophosphorus compound may cause damage to health, especially to the central nervous system. In the present work, we show the effects of chronic exposure of malathion on dendritic morphology of neurons from prefrontal cortex (PFC), hippocampus, and nucleus accumbens (NAcc) in adult male mice. Animals were injected i.p. with low dose of malathion (40 mg/kg body weight) for 14 days. Control animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Dendritic morphology was assessed in the prefrontal cortex, CA1 area of the hippocampus and the nucleus accumbens following repeated (14 days) low dose intraperitoneal application of OP malathion (40 mg/kg BW) in mice. Dendritic length in the hippocampus and prefrontal cortex, and density of dendritic spines in all the three areas assessed were reduced [25]. As part of the trisynaptic circuit, afferent inputs to the hippocampus are first sent to the dentate gyrus, which then projects to the CA3 area.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic morphology was assessed in the prefrontal cortex, CA1 area of the hippocampus and the nucleus accumbens following repeated (14 days) low dose intraperitoneal application of OP malathion (40 mg/kg BW) in mice. Dendritic length in the hippocampus and prefrontal cortex, and density of dendritic spines in all the three areas assessed were reduced [25]. As part of the trisynaptic circuit, afferent inputs to the hippocampus are first sent to the dentate gyrus, which then projects to the CA3 area.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were made out to a maximum of 200 mm from the soma and 20-30 mm dendritic segments were analyzed (n = 18-27 neurons for each studied genotype) and protrusions were measured as described previously. 59 No distinction was made between the different spine types. The analysis of dendritic morphology was performed using Zeiss LSM Image Browser software (Version 4.2) by research assistants who were blind to genotypes and experimental manipulations.…”
Section: P38mentioning
confidence: 99%
“…This process may play a critical role in producing the effects of DA-releasing stimulants, such as cocaine, on addiction-related neuroadaptation [17, 18]. The main targets of DA terminals in the PFC are pyramidal neurons, and the D1 receptor plays a particularly important role in mediating pyramidal cell morphogenesis after cocaine treatment [14, 19]. Importantly, recent studies have reported that repeated treatment of neurons with DA in vitro may model the effects of repeated cocaine use in vivo [20].…”
Section: Introductionmentioning
confidence: 99%